2018
DOI: 10.1080/22797254.2018.1544838
|View full text |Cite
|
Sign up to set email alerts
|

A review of seagrass detection, mapping and monitoring applications using acoustic systems

Abstract: Seagrass meadows are key elements of marine ecosystems as they affect the physical, chemical and biological environment and provide habitats for fish and invertebrates. Human activities have caused a deterioration in seagrass which has led to unstable benthic habitats; therefore, to prevent major decline, seagrass distribution must be mapped and monitored. Acoustic systems allow researchers, scientists and decision makers to collect highresolution datasets such as bathymetry, backscatter and sub-bottom profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 163 publications
(178 reference statements)
0
47
0
Order By: Relevance
“…To the best of our knowledge, there is no marine study yet that uses native PCLs for the investigation SAV or for habitat detection and classification, as presented here. The very recent review study regarding SAV mapping by Gumusay et al [22] lists several devices for seagrass detection and mapping, amongst which are single beam echosounders, acoustic doppler current profilers (ADCP), side scan sonars (SSS), MBES, and even low-cost recreational fishfinder-SSS. However, the authors only describe image-based approaches (SSS-and MBES-BS-mosaics, echograms, and WCI data) and features that are derived from DTMs, but do not mention the use of native MBES generated PCLs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, there is no marine study yet that uses native PCLs for the investigation SAV or for habitat detection and classification, as presented here. The very recent review study regarding SAV mapping by Gumusay et al [22] lists several devices for seagrass detection and mapping, amongst which are single beam echosounders, acoustic doppler current profilers (ADCP), side scan sonars (SSS), MBES, and even low-cost recreational fishfinder-SSS. However, the authors only describe image-based approaches (SSS-and MBES-BS-mosaics, echograms, and WCI data) and features that are derived from DTMs, but do not mention the use of native MBES generated PCLs.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed lab studies showed the dedicated backscattering response from the seagrass' tissue in the range of 0.5-2.5 kHz for three different seagrass species [21]. A recent review study by Gumusay et al [22] discusses seagrass detection with various acoustic systems between~1 and 1000 kHz.…”
Section: Mbes Seafloor Classification and Habitat Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective methods for mapping coastal habitats exist (e.g. Howard et al, 2014;Roelfsema et al, 2014;Gumusay et al, 2019) however mapping seagrass by remote sensing requires ground truthing and can be difficult because seagrasses are often submerged in turbid water and algal epiphytes may confuse spectral signatures. A knowledge of the extent of natural change is also needed (McKenzie, 2003).…”
Section: Seagrasses Occurrence and National Resource Quantification Imentioning
confidence: 99%
“…They also provide habitat for other organisms, such as juvenile fish and invertebrates. Numerous studies have documented the advantages of RS technologies for seagrass research: SRS [249,250], ARS [251], UAV [252] to USV, and SS [253]. To assess the state change of seagrasses, [229] presented an overview of the RS platforms that can be used to assess state changes, measure biophysical properties, map, monitor, and model the seagrasses ecosystem, as well as specifying the environmental conditions that do not allow the RS and their approaches to work.…”
mentioning
confidence: 99%